Biphenyl hydrogenation over supported transition metal catalysts under supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, C. V.; Sato, O.; Shirai, M. (Applied Catalysis A - General, 2005)
Catalytic hydrogenation of biphenyl to bicyclohexyl, an organic hydrogen storage medium, was examined over supported transition metal catalysts in supercritical carbon dioxide solvent. The yield of bicyclohexyl was almost 100% over the charcoal-supported rhodium (Rh/C) and ruthenium (Ru/C) catalysts at the temperature of 323 K, which was much lower than that required for biphenyl hydrogenation in organic solvents (573 K). The initial activity was higher over the Rh/C catalyst, while the initial selectivity to bicyclohexyl was higher over the Ru/C catalyst. The conversion of biphenyl increased with increase in hydrogen and carbon dioxide pressures, while the selectivity to bicyclohexyl was independent of hydrogen and carbon dioxide pressures over both catalysts. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: bicyclohexyl; biphenyl; charcoal-supported rhodium catalyst; charcoal-supported ruthenium catalyst; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide

Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin

Ring hydrogenation of naphthalene and 1-naphthol over supported metal catalysts in supercritical carbon dioxide solvent - Shirai, M.; Rode, C. V.; Mine, Eiichi; Sasaki, A.; Sato, O.; Hiyoshi, Norihito (Catalysis Today, 2006)
Catalytic ring hydrogenations of naphthalene and 1-naphthol were studied over several supported metal catalysts in supercritical carbon dioxide solvent at low temperature. Higher concentration of hydrogen in supercritical carbon dioxide and lower reaction temperature were responsible for higher catalyst activity and selectivities to the desired partial ring hydrogenated products as compared with those observed in organic solvent for the same catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 1-naphthol; Hydrogenation; Naphthalene; Supercritical carbon dioxide; supported metal catalyst

Selective catalytic oxidation of geraniol to citral with molecular oxygen in supercritical carbon dioxide - Dapurkar, Sudhir E.; Kawanami, Hajime; Chatterjee, Maya; Rode, Chandrasekhar V.; Yokoyama, Toshirou; Ikushima, Yutaka (Applied Catalysis A-General, 2011)
Selective catalytic oxidation of geraniol to citral with molecular oxygen in supercritical carbon dioxide (scCO(2)) has been investigated. The catalyst used was a chromium containing mesoporous molecular sieve catalyst viz. CrMCM-41. Comparison studies were performed with CoMCM-41. PtMCM-41 and PdMCM-41 catalysts. Among the various catalysts studied. CrMCM-41 showed a high conversion of geraniol and an excellent selectivity for citral. In contrast CoMCM-41, PtMCM-41 and PdMCM-41 catalysts exhibited low conversion of geraniol. However all three catalysts compared showed similar citral selectivity to CrMCM-41. The effect of CO(2) pressure and reaction temperature geraniol oxidation was studied with CrMCM-41. Supercritical CO(2) medium was found to enhance the conversion of geraniol and/or yield of citral. It was noticed that the catalyst can be recycled with negligible loss of conversion. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Citral; Geraniol; heterogeneous catalyst; Molecular oxygen; Selective oxidation; Supercritical carbon dioxide

Reactions in supercritical carbon dioxide - Mayadevi, S. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Use of conventional organic solvents often leads to the formation of hazardous waste, the disposal of which is a matter of environmental concern. Carbon dioxide is considered to be a green reaction medium and a good replacement for conventional organic solvents as it is benign and leads to elimination/reduction of hazardous wastes. Use of CO2 at near/above critical conditions has several additional advantages as the reactions can be pressure-tuned to eliminate transport resistance, increase solvent power and heat capacity. Hence, there has been considerable interest in the use of supercritical carbon dioxide as either a replacement of conventional organic solvent or as a co-solvent in reactions. Herein, recent developmenst in this area during the last decade is reviewed, specifically in gas-liquid (organic hydrogenation, hydroformylation and oxidation) and liquid-liquid (carbon-carbon coupling, alkylation, acetylation, esterification) reactions.
Keywords: Alkylation; Carbon dioxide; Hydroformylation; Hydrogenation; Oxidation; Supercritical carbon dioxide

Reduction of carbon dioxide to dimethylformamide using ruthenium doped Mg/Al hydrotalcites under supercritical conditions - Chaudhary, Sagar D.; Rahatade, Shardul S.; Joshi, Sunil S.; Mali, Nilesh A. (Journal of CO2 Utilization, 2022)
The utilization of carbon dioxide is one of the developing areas due to its significant contribution to global warming. Reducing carbon dioxide (CO2) to formic acid and its derivatives has gained importance because of its thermodynamic limitations and high industrial demand. In this article, we report the synthesis of dime-thylformamide (DMF) using ruthenium doped Mg/Al calcined hydrotalcite by CO2 hydrogenation in the presence of dimethylamine (DMA). At optimized conditions, complete conversion of dimethylamine was achieved with more than 92% product yield at 170 degrees C and 13 MPa pressure with a reaction time of 6 h. Key catalyst properties were determined using X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), CO2-temper-ature programmed desorption (TPD), H-2 temperature-programmed reduction (TPR) and Fourier transform infrared (FTIR). The determination of surface morphology was carried out using field emission scanning electron microscope (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). At the same time, the chemical composition was verified by energy-dispersive X-ray (EDS). In addition, kinetic modeling is performed using the two site Langmuir-Hinshelwood-Hougen-Watson model. The regressed kinetic parameters gave an appropriate fit with experimental concentration values and activation energy is calculated as 413 kJ/mol K-1.
Keywords: Dimethylformamide; Hydrogenation; hydrotalcite; Langmuir-Hinshelwood-Hougen-Watson model; Supercritical carbon dioxide